2021
DOI: 10.1155/2021/6149558
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 Intensifies the Progress of Oral Squamous Cell Carcinoma via Modulating the m6A Amount of PRMT5 and PD-L1

Abstract: N6-Methyladenosine (m6A) modification is one of the commonest chemical modifications in eukaryotic mRNAs, which has essential effects on mRNA translation, splicing, and stability. Currently, there is a rising concern on the regulatory role of m6A in tumorigenesis. As a known component in the m6A methyltransferase complex, METTL3 (methyltransferase-like 3) plays an essential role in m6A methylation. Till now, the functions of METTL3 in oral squamous cell carcinoma (OSCC) and its relative mechanism remain to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 33 publications
(37 reference statements)
2
27
0
Order By: Relevance
“…Studies have shown that the risk score composed of the m 6 A gene is related to the in ltration of dendritic cells, neutrophils, CD4 + T cells, CD8 + T cells, and B cells, and upregulated m 6 A regulators are positively correlated with PD-L1 in the HNSCC tumor immune microenvironment [38]. Ai Y et al found that highly expressed METTL3 promotes the progression of oral squamous cell carcinoma by inhibiting the activation of CD8 + T cells and modulating the m 6 A levels of PRMT5 and PD-L1 [39]. Other researchers have found that METTL3 is upregulated and associated with poor prognosis in oral squamous cell carcinoma [40], which was consistent with our study although the difference was not signi cant (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the risk score composed of the m 6 A gene is related to the in ltration of dendritic cells, neutrophils, CD4 + T cells, CD8 + T cells, and B cells, and upregulated m 6 A regulators are positively correlated with PD-L1 in the HNSCC tumor immune microenvironment [38]. Ai Y et al found that highly expressed METTL3 promotes the progression of oral squamous cell carcinoma by inhibiting the activation of CD8 + T cells and modulating the m 6 A levels of PRMT5 and PD-L1 [39]. Other researchers have found that METTL3 is upregulated and associated with poor prognosis in oral squamous cell carcinoma [40], which was consistent with our study although the difference was not signi cant (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…METTL3 regulates the m6A levels on EZH2, tankyrase and snail and promotes the progression of nasopharyngeal carcinoma [296][297][298]. METTL3 may regulate the expression of PRMT5, PD-L1 and c-MYC through m6A to promote the progression of oral squamous cell carcinoma [299,300]. YTHDC2 physically binds to insulin-like growth factor 1 receptor (IGF1R) mRNA to promote the translation of IGF1R mRNA, which in turn activates the IGF1-AKT/S6 signaling pathway and promotes radiotherapy resistance in nasopharyngeal carcinoma cells [301].…”
Section: Head and Neck Cancermentioning
confidence: 99%
“…METTL3 mediates the RNA methylation modification process and functionally catalyzes m6A mRNA methylation [ 89 ]. By increasing the m6A content in protein arginine methyltransferase 5 (PRMT5) and PD-L1, METTL3 promotes the metastasis and proliferation of OSCC [ 90 ]. Through a m6A-dependent mechanism, METTL3 positively regulates IGF2BP3 to increase the stability and expression of PD-L1 mRNA in BC [ 91 ].…”
Section: N6-methyladenosinementioning
confidence: 99%
“…MLL1 ↑PC [134] NRF2 ↑HCC [22] ATF3 ↑melanoma and NSCLC [55] Epigenetic regulation of PD-L1 DNA methylation ↓melanoma [62,64], leukemia [39] Histone modification ↓BC and B cell lymphomas [53,185], lung cancer [66] MicroRNAs shown in Table 1 N6-methyladenosine ↑OSCC [90], ↑BC [91] LncRNA and circRNA HOTTIP, SNHG12, EMX2OS-↑OC[76, 77, 81] SNHG20-↑esophagus cancer [78] CASC11-↑HCC [80] SNHG14-↑DLBCL [79] NUTM2A-AS1-↑GC [82] Hoxa-AS2-↑nasopharyngeal carcinoma [83] IFITM4P-↑OSCC [84] LncMX1-215-↓HNSCC [85] Hsa_circ_0000190-↑NSCLC [186] HasCircRNA-002178-↑ LUAD [87] CDR1-AS-↑CC [88] PD-L1 regulation at the protein level Ubiquitination ↓ BC [97], NSCLC [98], CC [99], colon cancer [100], melanoma [101,102,106], lung cancer [101], esophageal squamous cell carcinoma [105] Glycosylation ↑AML [108], TNBC [109,111], colon cancer [110], prostate cancer [111], glioma [112] Phosphorylation ↓ BC [114,116], HCC [115] Acetylation ↓ multiple cancers [117] Palmitoylation ↑ BC and colon cancer [118,…”
Section: Regulators Of Pd-l1 Cancer Typementioning
confidence: 99%